THE EFFECTIVENESS OF SOCIO-SCIENTIFIC ISUES-BASED ELECTRONIC STUDENT WORKSHEET TO IMPROVE CRITICAL THINKING SKILLS FOR CLASS VII STUDENTS - Evi Normawati; Sifak Indana; Tarzan Purnomo (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2022)
Technological developments have affected all aspects of life, including education. Advances in technology require people to be technologically literate. In addition, the occurrence of the COVID-19 pandemic also requires learning to be carried out online. This requires teachers to be able to develop teaching materials that can be accessed easily by students during the learning process. The learning process must also support the achievement of 21st-century skills, one of which is critical thinking. SSI-based learning can train critical thinking skills. The purpose of this study was to determine the effectiveness of the Electronic Student Worksheet based on socio-scientific issues (SSI) on environmental pollution materials to train the critical thinking skills of class VII students. The implementation was carried out on three class VII study groups using the One-Group Pretest-Posttest Design. Effectiveness in terms of increasing critical thinking skills during the learning. The improvement in critical thinking skills of students in grades VII-1, VII-3, and VII-4 is significant in the moderate category, with an N-Gain score of 0.48, 0.52, and 0.51. The student's response is positive, with a mode value of 4.